Pengaruh Iklim Kerja, Kompensasi, dan Kompetensi terhadap Produktivitas Kerja pada STMIK Dharma Putra - I Gusti Made Karmawan; Winanti Winanti; Sugiarto Hartono (Bina Nusantara University, 2015)
Compensation is everything that will be received by a person as remuneration for the work she/he has done, either directly or indirectly. Assessment of labor productivity is almost always automatically associated with the rules and regulations of individual salary increases and bonus distribution. Result of the analysis indicates work environment played a very important role for the improvement of labor productivity with r2 = 0.933 (93.3%), and t 8.158 and t table 0.30. Result of the hypothesis testing of the effect of compensation onemployee and lecturer productivity (r2=0.933 or 93.3 % with t 3.729 and t table of 0.30) means compensation had a very strong influence. Result of the hypothesis testing of the effect of competence on employee and lecturerproductivity shows r2= 0.933 or by 93.3%, with t 4.014 and t table 0.30. Result of the analysis shows the correlation between work environment and labor productivity is equal to 0.769, means it had a fairly high correlation. The correlation between compensation and labor productivity by 0.482 is moderate. The correlation between competence and labor productivity by 0509 is moderate. The determination determination is equal to 0.933 means that employee and lecturer productivity was influenced by work environment, compensation, and competency in the amount of 0.933 (93.3%); while the 6.7% remaining was influenced by other variables outside the research. The regression function resulted from the analysis is Y = -0.026 + 0.548 X1 + 0.260 X2 + 0.281 X3.